PREPARATION OF THE FUTURE TEACHER IN THE CONDITIONS A STUDENT-CENTERED EDUCATIONAL PARADIGM - Zhanguzhinova, Meruyert; Magauova, Akmaral; Sydykova, Rosa; Yermekova, Zhadyra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The system of education at the present stage of social development is undergoing the significant changes, which are characterized by strong innovative processes demanded by the mass participation of teachers in these processes. The Medium-Term Strategy as a basis for further development of the education system is determined by the needs in teacher training, ready to work in a high-tech learning environment. As a result of innovative processes taking place in modern society is developing a new system of educational values.